Analitični pogled na najvidnejše družbene medije v letu 2023 (University of Maribor Press, 2023)
An Analytical Overview of the Most Prominent Social Media in 2023. The publication "An analytical overview of the most prominent social media in 2023" addresses a recognised research gap in the study of the social media design. In doing so, particular emphasis is placed on the conceptual aspect, which allows for the identification of the logical design, architectural features, potentials and specificities of social media, as well as for comparison with competing solutions. The publication is a collection of inter-comparable chapters that descriptively and analytically examine the most prominent representatives of the social media landscape in 2023. The chapters are the result of a project assignment of students from the University of Maribor, Faculty of Electrical Engineering, Computer Science and Informatics, who systematically and under supervision studied selected social media in the framework of the course "Architecture of Interactive Media Content".